(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2022)
The article examines the reasons for the beginning, the legal basis, the procedure for carrying out "purges" in state organizations conducted in 1929-1932, and the consequences on the example of the Fergana Valley.